Budget execution of spending an issue to improve in public institutions (2015)
This paper will turn to improve the budget execution of public entities Colombian State in accordance with the financial resources allocated by the National Planning Directorate, General Budget of the Nation and the Ministry of Public Finance for a fiscal year.